La chuscada Ancashina and its adaptation process for solo guitar: Javier Molina and Jacinto Palacios - Ramos Salazar, Brahayan Jesús (2022)
The chuscada, or huayno ancashino, is a genre that is part of the traditional Andean music of Peru, which has gained great popularity in recent years as a result of the interpretations of various folk singers. This genre, in addition to being performed jointly, that is, with a group that accompanies the singer, can also be performed in other formats. The guitar is part of the instruments with which it is usually played and accompanied, and thanks to its adaptability it makes it possible for the ancashina chuscada to be interpreted in a solo version. This article analyzes the Ancash chuscada and its adaptation for guitar, also contains a section that reviews the various theories to make clear the conceptualization of the proposed categories. Likewise, the results obtained from the interviews carried out with musicians with a recognized career in the solo guitar of this genre are included, since their experience and contributions allow us to know and understand how the problem of musical adaptation develops, helping to formulate the conclusions. Finally, the article presents a description of the process of adapting the chuscada for its performance on the solo guitar, in addition to exposing the aspects and stages that are taken into consideration throughout this process. It is concluded that the contribution of Javier Molina values the work of Jacinto Palacios, the fact that he has selected works by this composer to carry out his adaptations is proof of his great influence in the Andean musical field, and that for this reason it is necessary transmit and record your music through your musical adaptations, arrangements and transcriptions. On the other hand, knowing the process of adaptation of the chuscada on the solo guitar contributes to enriching the knowledge and the way in which an arrangement and adaptation of Ancash music should be carried out, since not everyone has or knows the patterns that are necessary to carry out this process. Finally, the assimilation of the information that in this article serves as a guide and incentive for Andean solo guitar players to dare to make adaptations and arrangements of Ancash music or Peruvian music of any style that has not been performed up to now. the same that will be able to contribute to the increase of the repertoire for solo guitar.